Effect of bagasse ash and filter cake amendments on wheat (Triticum turgidum L.var. durum) yield and yield components in nitisol - Assefa Gonfa; Bobe Bedadi; Anteneh Argaw (International Journal of Recycling of Organic Waste in Agriculture, 2018)
Abstract Purpose This experiment was initiated to evaluate the effect of filter cake and bagasse ash on the productivity of wheat under greenhouse conditions. Methods Six levels of filter cake and bagasse ash each separately and control check were arranged in a completely randomized design with three replications. Results At 100 tons/ha, both inputs resulted in the highest values of all the investigated traits. It was also found that yield and yield components that were obtained from bagasse ash overwhelmed those from filter cake treatments, except in tillers, dry biomass, and straw yield. Linear regression analysis revealed a significant and positive relationship between grain yield with that of total N, P, K, S, Ca, Mg, Cu, and Zn uptake. A linear relationship between the grain yield with that of N and Zn uptake was found, while the association between grain yield with total P, K, S, Ca, Mg and Cu uptake was quadratic. Conclusion It can be concluded that filter cake and bagasse ash are good sources of nutrients to enhance wheat yield in acidic soil. To give a conclusive result, these inputs should be tested in field trials in different soil types.